DESIGN OF BORED PILE AND LIQUEFACTION ANALYSIS OF ELEVATED RAILROAD BRIDGE FOR FREIGHT TRAINS IN TANJUNG PERAK - NURSYAHARANI SALIM - NIM : 15014011 , RATIKA
Tanjung Perak Elevated Railroad Bridge is an infrastructure that connects the harbor with the hinterland, in an effort to overcome the problem of congestion in container flow mobilization to the hinterland area due to the increasing demand of container goods in Tanjung Perak. And geotechnical aspects is one among other aspect of this bridge project planning. This publication discusses the planning of bored pile foundation, pile cap, and also analysis of potential liquefaction in the project area. The loading used in the bored pile planning uses the results of the upper structure modelling, then the Allowable Stress Design (ASD) analysis is performed to determine the permission strength limit, which consists of checking the axial and lateral pile capacity and also settlement of the pile group. Analysis of Load and Resistance Factor Design (LRFD) method is used for reinforcement of bored piles and pilecap. The design of this foundation refers to the requirements required by AASTHO LRFD Bridge Design. Meanwhile, liquefaction potential analysis using NCEER method. From the analysis, there are three types of configuration of the pile group, which is 6x6, 5x5, 4x4, each of individual piles has a diameter of 800 millimeters and 37 meters long. Then, the result of liquefaction analysis showed that liquefaction occurred at 10 meter at the top layer of soil in this project area.